Application of Doppler echocardiography and tissue Doppler Imaging in the evacuation of cardiac function of normal cats and cats with hypertrophic cardiomyopathy - Koffas, Haralambos (The University of Edinburgh, 2004)
Hypertrophic cardiomyopathy (HCM) of cats is the most common cardiac disease of this species. Feline HCM shares many of the morphological characteristics recorded with human HCM. Diastolic impairment is believed to be the main abnormality of the disease and evidence for this has been provided by both invasive and Doppler echocardiography studies. Tissue Doppler Imaging (TDI) has emerged in the last decade as an alternative tool for the non-invasive quantification of regional and global myocardial function. TDI studies in affected humans and experimental animals have shown that systolic impairment is also evident in HCM, despite the presence of normal or supernormal contractile state of the LV in this cardiac entity. The aims of this study were (1) to produce Doppler echocardiographic criteria of normality in cats; (2) to identify differences in ventricular function using Doppler echocardiography between normal cats and cats with HCM; (3) to investigate diastolic and systolic function in normal cats and cats with HCM, by means of TDI. There was no significant difference in LV FS% between normal and HCM cats although affected cats tended to have higher FS%. Apart from the E deceleration time of mitral inflow, which was prolonged in HCM cats, neither the E/A of mitral inflow nor the FVRT were different between the two groups. The LV flow propagation velocity was significantly lower in the affected group compared to that in normal. Asymptomatic affected cats had a higher S wave and S/D ratio and a lower D wave of pulmonary venous flow (PVF) than normal cats. The time from the Q wave of the ECG to peak systolic velocities of PVF was significantly prolonged in the HCM than in the normal group. HCM cats showed significantly higher aortic and pulmonic velocities than normal cats. The TDI technique revealed evidence of both diastolic and systolic dysfunction in HCM cats. On pulsed TDI data, diastolic dysfunction was expressed with decreased early diastolic velocities, lower early diastolic acceleration and deceleration, prolonged IVRt and decreased E'/A', mainly along the longitudinal axis of the heart. The physiologic time and space non-uniformity recorded in the LV motion of normal cats was lost in affected cats. Systolic dysfunction in the HCM group was less prominent than the diastolic, and was expressed with decreased late systolic velocities and systolic acceleration mainly along the longitudinal axis. This decrease was independent from left ventricular out-flow tract obstruction and was present in asymptomatic affected cats. Cats with CHF showed a tendency for decreased systolic myocardial indices. On colour M-mode TDI, certain colour velocity stripes were appeared on the LVPW of cats and were corresponded to certain peaks occurring in tracings of both the Myocardial Velocity Gradients (MVG) and Mean Myocardial Velocity (MMV). Biphasic shifts were recorded in the LVPW during early diastole and the two isovolumic periods. MVG followed wall thickness changes during the different phases of the cardiac cycle. Peak MVG during early diastole and systole was significantly reduced in HCM cats compared to that in normals. Peak MMV during the second phase of the isovolumic contraction period was significantly reduced in HCM cats This study, for the first time, offers evidence for systolic dysfunction in feline HCM. The data presented here provide reference data for future studies in the investigation and better classification of feline cardiac diseases. The successful application of TDI in cats, despite the very small size of their heart and the inherent high heart rates often encountered in this species, provides evidence for possible successful application of the technique in human neonatal hearts and experimental small animal models of human diseases.
An application of Doppler echocardiography and tissue Doppler Imaging in the evacuation of cardiac function of normal cats and cats with hypertrophic cardiomyopathy